Efeitos da integração vertical na sustentabilidade dos empreendimentos rurais: o caso da goiaba no estado de São Paulo. - Lopes, Luciene de Andrade Bianchi (Universidade Federal de São Carlos, 2006)
The vertical integration used in to guava production in São Paulo state is presented as a strategy which helps the agricultural producers in the gradual reach of the business sustainability in the economic, social and environmental dimensions. The aim of this work was to study the agricultural enterprises management which are directed to guava production destined to processing in the biggest producing region of São Paulo state, comparing, through the indicators, the verified results in the agricultural enterprises in which the production verticalization was used, to the obtained ones by the producers who produce the raw material and deliver it to the processing. The study method of multiple cases was chosen for the accomplishment of the work empirical part. It was observed that characteristics such as scholarship low level and the familiar labor participation are common to almost all studied producers, being or not own raw material processors. It was also observed that, only the agricultural producers, who process their productions and are considered great, control the guava production costs. It is verified that the value aggregation to the raw material before trading really contributes for the reach of an agricultural business better performance in the economic, social and environmental dimensions. The main advantage for the producers who verticalized their productions is the best remuneration gotten for the raw material, contributing for the permanence in the sector and reducing the dependence of the raw material sales business for the region processors. The local development as a result of the value aggregation is also verified, through more work ranks generation, income distribution and life quality improvement of the involved ones. Amongst the restrictions of the production verticalization the management tools use absence is emphasized, information register and analysis methods, entry difficulty in the markets for the products trading, specially the international ones, and the price competition of the small clandestine processor products. The majority of the producers did not professionalize the management of their businesses mainly for cultural questions which bring from the land succession process, no matter adding or not value to the production. This study shows the necessity of changing the agricultural producer profile and evidences of adding value to his production is a suitable way to reach the sustainability and the sector permanence.
Vertical integration effect in agricultural enterprises sustainability: the guava case in São Paulo state.
Keywords: Desenvolvimento sustentável; Integração vertical; Cadeias agroindustriais - coordenação; Goiaba; Valor adicionado; Sustainability; Adding value; Verticalization; Guava; ENGENHARIAS::ENGENHARIA DE PRODUCAO